COMUNICAÇÃO E COMPARTILHAMENTO DE CONTEÚDO: O USO DE RECURSOS EDUCACIONAIS ABERTOS POR DOCENTES DA UMESP - Sampaio, Paulo Sergio (2013)
In the scope of Communication Rights, Human Rights and of the discussion regarding Copyright about works mainly Literary and Scientific, this work has as the main goal the development and appliance of a field-work of an exploratory character. It seeks to establish a mapping of the use of production and sharing practices of open content by UMESP faculty, through the use of free licensing Commons type and following the precepts proclaimed by Open Educational Resources (OER) movement. Thus, the statistical method used was the simple random probabilistic sampling using a questionnaire with closed questions, enabling the elaboration of a consistent database that was exploited in order to confirm the hypothesis previously formulated, besides to contemplate others inferences no less interesting. The main conclusion is that, even if not being knowledge of the majority faculty of UMESP about sharing content under license free and neither about the OER movement, there are no significant constraints regarding adherence to such practices.